Efficacy and safety of tenofovir, entecavir, and telbivudine for chronic hepatitis B in heart transplant recipients. Issue 3 (10th May 2016) - Durante‐Mangoni, E.; Vitrone, M.; Parrella, A.; Andini, R.; Iossa, D.; Ragone, E.; Falco, E.; Maiello, C.; Utili, R.; Zampino, R.
Abstract: Background: Treatment of chronic hepatitis B (CHB) with polymerase inhibitors is key to prevent disease flares and progression toward advanced liver disease. Efficacy and tolerability of newer agents has been reported anecdotally in transplant recipients. Methods: In this prospective, observational study, we assessed outcomes of therapy with tenofovir (TDF), entecavir (ETV), and telbivudine (LdT) in 13 heart transplant recipients (HTR) with CHB. Results: Most patients were hepatitis B e antigen negative, had low baseline hepatitis B virus (HBV) DNA, and normal aminotransferases. Liver biopsy showed a median fibrosis score of 1.5 (range 0–4). Glomerular filtration rate (GFR) was <50 mL/min in 7 patients (54%). Two patients were started on de novo ETV before transplant. Eleven previously treated patients were switched to TDF ( n = 9) or LdT ( n = 2). Median treatment duration was 33 months (range 1–71). HBV DNA remained suppressed in 6 patients and became undetectable in 5. Aminotransferases went down to the normal range in all patients, with a single flare in 1 patient. One patient lost hepatitis B surface antigen. No cases occurred of hepatic decompensation, hepatocellular carcinoma, or liver‐related death. The GFR remained largely stable, and no cases of TDF‐related hyper‐phosphaturia were observed. Conclusions: This study indicates that newer antivirals are effective and safe in HTR with CHB.